Assistance for the Prescription of Nutritional Support Must Be Required in Nonexperienced Nutritional Teams - Mehdi Ouaïssi; Philippe Grandval; Diane Mege; Anamaria Nedelcu; Gaëlle Hautefeuille; Frédéric Vanhoeve; Bernard Sastre; Igor Sielezneff; Jacques di Costanzo (Journal of Nutrition and Metabolism)
The aim of the study was to determine the current practices of nutritional support among hospitalized patients in nonspecialized hospital departments. Materials and Methods. During an observation period of 2 months, a surgeon and a gastroenterologist designated in each of the two departments concerned, not “specialized” in nutritional assistance, have treated patients in which nutritional support seemed necessary. Assessing the degree of malnutrition of the patient, the therapeutic decision and the type of product prescribed by the doctors were secondarily compared to the proposals of a structured computer program according to the criteria and standards established by the institutions currently recognized. Results. The study included 120 patients bearing a surgical disease in 86.7% of cases and 10% of medical cases. 50% of the patients had cancer. Nutritional status was correctly evaluated in 38.3% by the initial doctors’ diagnosis—consistent with the software’s evaluation. The strategy of nutrition was concordant with the proposals of the software in 79.2% of cases. Conclusions. Despite an erroneous assessment of the nutritional status in more than two-thirds of cases the strategy of nutritional management was correct in 80% of cases. Malnutrition and its consequences can be prevented in nonexperienced nutritional teams by adequate nutritional support strategies coming from modern techniques including computerized programs.